EVALUATION OF CHILDREN MARRIAGE PREVENTION POLICY IMPLEMENTATION IN DOMPU DISTRICT IN 2016-2021 - Imam Alfafan; M. Mas'ud Said; Ali Masykur Musa (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Dompu Regency is one of the regencies in West Nusa Tenggara Province with the highest number of child marriage cases. There has been a decrease in the number of cases from year to year. This is a good implication of the implementation of local government policies. The study aims to describe and analyze the process and results of the implementation of the policy to prevent child marriage in Dompu Regency for the 2016-2021 period. The study use descriptive analytical method with a qualitative approach. Conducted at the Kantor Perlindungan Pemberdayaan Perempuan dan Anak (DP3A) Kab. Dompu in May 2021. Data collection techniques used interview, observation, and documentation techniques. The data analysis technique used was qualitative consisting of data reduction, data presentation, and drawing conclusions by applying inductive logic. The results showed (1) DP3A Dompu Regency implemented several policies to overcome the problem of child marriage. In the period 2016-2021, policies have been implemented to establish the Komisi Perlindungan Anak Desa (KPAD), the Simultaneous Movement Module Program, the creation of Adolescent Reproductive Health Education for each SMP/MTs and SMA/MA/SMK, and the selection of peer counselors. Some of these policies are the result of the formulation and agreement process and are implemented by the Dompu Regency DP3A together with local NGOs and NGOs. (2) The implementation of the policy to prevent child marriage is considered successful in preventing an increase in cases of child marriage; Dompu local government policies currently have an impact on public understanding of the risks of child marriage. (3) the policy becomes a program that only prioritizes sensation and mere formality, costs a lot of money, has incomplete impacts and targets, is faced with difficult regulatory conditions, so that some programs cannot be implemented optimally and have a more positive impact.